Determination of Purchasing Decisions through Purchase Interest: Analysis of Somethinc Skincare Product Quality - Siska Aprelyani (Siber Nusantara Research, 2024)
This article discusses the influence of Product Quality through Purchase Decisions on Purchase Intention. This research is a quantitative research where the objects used are Generation Z in Bekasi City. The number of samples used in this study was 200 respondents. The design used is hypothesis testing using the structural equitation model (SEM) method - SmartPLS 4.0. Based on the conceptual framework created, it can be concluded that the hypothesis is that product quality has an effect on purchase interest and purchase decisions.